Clinical Characteristics of 10 Pregnant and Postpartum Women With Extracorporeal Membrane Oxygenation: A Retrospective Study - Gu, Qiao; Peng, Weihua; Zhu, Ying; Xi, Shaosong; Diao, Mengyuan; Hu, Wei; Zeng, Xiaokang (Frontiers in Medicine, 2022)
Background: The aim of study was to summarize the clinical characteristics and experience of extracorporeal membrane oxygenation (ECMO) in pregnant and postpartum patients. Methods and Results: We retrospectively reviewed 131 consecutive ECMO patients at our center from May 2015 to May 2021. A total of 10 Chinese patients were pregnant or postpartum at the time of ECMO initiation. Patients ranged in age from 25 to 36 years (median age 30.5 years). The ECMO duration ranged from 3 to 31 days (median duration 8 days). There was a stabilizing trend of acid-base balance and decreasing lactic acid over the three days following ECMO initiation. Seven (70%) patients survived at least 48 hours after weaning from ECMO. Four (40%) patients survived until discharge, and four (40%) fetuses survived until discharge. Conclusion: ECMO provides a suitable temporary cardiopulmonary support for pregnant and postpartum patients. ECMO shows a favorable effect on short-term stability in critical obstetric patients.